A Deep Reinforcement-Based Anomaly Intrusion Detection for Enhancing Network Cybersecurity - Mohammed Tuaama, Maytham (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Conventional protection methods, such as rules-based firewalls and signature-based detection, are not cutting it in today's environment of increasingly sophisticated and frequent cyberattacks. Cyberattacks nowadays are extremely dynamic and complex, calling for cutting-edge solutions that can change and adapt as the threat does. DRL is an AI subfield that has been successfully addressing difficult decision-making challenges in several fields, including cybersecurity. Here, we make a step forward by using a DRL framework to model cyberattacks; by incorporating real-world events, we make the models more realistic and applicable. We provide a customized approach that greatly improves existing approaches by carefully tailoring DRL (deep reinforcement algorithms to the complex needs of cybersecurity situations, including adversarial training, dynamic environments, bespoke structure of reward and actions, and more. In this study, we provide an anomaly detection method to detect attacks on network CPS using Deep Reinforcement Learning. Our proposed methodology was tested using several publicly available research datasets to ensure its efficacy.